Evaluation of sleep and treatment discipline in people with epilepsy - D. Streckytė; R. Mameniškienė (Neurologijos seminarai)
ntroduction. Antiepileptic drugs are effective in treating epilepsy and about 70% of people with epilepsy can be seizure-free; however, undisciplined use of antiepileptic drugs is a major cause of treatment failure. The aim of the study. To study the discipline of sleep and treatment regimen in people with different types of epilepsy and evaluate their determinants. Methods. A cross-sectional questionnaire-based study of adults with epilepsy who received antiepileptic treatment. Statistical analysis was performed using MS Excel and SPSS 21.0 pro- grams. Statistical significance was defined with a p<0.05. Results. The study included 100 participants, 65% had focal epilepsy and 55% were women. The median age was 37.5±15.7, mean epilepsy duration – 9.5±11, mean age of epilepsy onset – 21.5±17 years. It was found that 30% of participants did not adhere to their treatment regardless of epilepsy type (p=0.819). Nonadherence was associated with living in a rural area (p=0.032), frequent seizures (p=0.033), and less frequent medication dosing (p=0.032), especially in generalized epilepsy group (p=0.019). Sleep regimen did not depend on epilepsy type (p>0.05), 35% of respondents slept less than 7 hours per night, and 53% did not follow sleep regimen, which was related to treatment indiscipline (p=0.027). Conclusions. Nonadherence to the antiepileptic drugs is common among people with epilepsy. The most common subjective reason is forgetfulness, while objective reasons are living in a rural area, frequent seizures, and less frequent dosage of the antiepileptic drug. More than half of people with epilepsy do not follow a regular sleep regimen and tend to disregard treatment regimen.